2014
DOI: 10.1126/science.1252480
|View full text |Cite
|
Sign up to set email alerts
|

Lassa virus entry requires a trigger-induced receptor switch

Abstract: Lassa virus spreads from rodents to humans and can lead to lethal hemorrhagic fever. Despite its broad tropism, chicken cells were reported to resist infection thirty years ago. We show that Lassa virus readily engaged its cell surface receptor α-dystroglycan in avian cells, but virus entry in susceptible species involved a pH-dependent switch to an intracellular receptor, the lysosome-resident protein LAMP1. Iterative haploid screens revealed that the sialyltransferase ST3GAL4 was required for the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
361
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(393 citation statements)
references
References 43 publications
20
361
1
1
Order By: Relevance
“…This places dystroglycan amongst other important pathogen receptors, including the transferrin receptor, noted for efficient internalization of extracellular ligands (Choe et al, 2011). Interestingly, LCMV and LASV have also been shown to traffic to the late endosomes, multivesicular bodies and lysosomes, mirroring our results for laminin and dystroglycan trafficking (Jae et al, 2014;Pasqual et al, 2011). Our observations of laminin trafficking to the late endosome and lysosome are supported by previous electron microscopic imaging of gold-labeled laminin-111, which revealed laminin accumulation in non-coated pits at the cell surface and in multivesicular bodies (Coopman et al, 1991).…”
Section: Discussionsupporting
confidence: 72%
“…This places dystroglycan amongst other important pathogen receptors, including the transferrin receptor, noted for efficient internalization of extracellular ligands (Choe et al, 2011). Interestingly, LCMV and LASV have also been shown to traffic to the late endosomes, multivesicular bodies and lysosomes, mirroring our results for laminin and dystroglycan trafficking (Jae et al, 2014;Pasqual et al, 2011). Our observations of laminin trafficking to the late endosome and lysosome are supported by previous electron microscopic imaging of gold-labeled laminin-111, which revealed laminin accumulation in non-coated pits at the cell surface and in multivesicular bodies (Coopman et al, 1991).…”
Section: Discussionsupporting
confidence: 72%
“…Genome-wide genetic screening in human haploid cells is a powerful tool to reveal host factors involved in entry of various pathogens, including viruses (15,16). In this study, we performed a haploid screen and demonstrate that genes involved in synthesis of sialylated glycans are essential for EV-D68 infection.…”
mentioning
confidence: 99%
“…In a recently described structure of the GPC protein from lymphocytic choriomeningitis virus (LCMV) in a prefusion conformation (26), the histidines that are homologous to His92 and His93 are in a slightly different orientation compared to that seen for isolated Lassa virus GP1 and have close contacts with other residues. Although LCMV enters cells independently of LAMP1 (11,26), the GP1 subunit of LASV may adopt a prefusion conformation similar to that observed in the LCMV structure. If this is true, it may explain the lower tolerance for mutation of His92 and His93.…”
Section: Discussionmentioning
confidence: 99%
“…Three fully processed glycoprotein moieties comprise the functional trimeric spike complex. It was recently shown that successful infection by LASV requires it to switch in a pH-dependent manner from the primary ␣-DG receptor to lysosome-associated membrane protein 1 (LAMP1) (11). LAMP1 (also called CD107a) is a major constituent of the lysosome membrane (12) and is thought to play an important role in maintaining lysosome integrity (13).…”
mentioning
confidence: 99%